2023
DOI: 10.15294/efficient.v6i1.55232
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Agglomeration and Economic Growth in Indonesia

Adinda Dwi Nurlestari,
Shanty Oktavilia

Abstract: This study aims to analyze the level of industrial agglomeration using balassa index and spatial analysis. In addition, this study also analyzes the effect of industrial agglomeration, investment, infrastructure, and inequality on economic growth. The data used in this study are secondary data. This study uses panel data regression with a fixed effect model approach, consisting of 34 provinces in Indonesia for the period 2015-2020. The results of this study indicate that industrial agglomeration occurs in 7 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Hence, knowledge transfer among female workers occurs mostly within firms in Java. These results are likely related to industrial development, clustering effects, agglomeration, and other forms of geographical concentration that are more pronounced on Java Island than in regions outside Java (Kuncoro & Wahyuni, 2009;Nurlestari & Oktavilia, 2023). The literature on MNCs spillover effects suggests that positive effects of inter-industrial spillovers are more often found than intraindustry ones (Rojec & Knell, 2018).…”
Section: Estimation Results For Java (National Industrial Corridor) A...mentioning
confidence: 93%
“…Hence, knowledge transfer among female workers occurs mostly within firms in Java. These results are likely related to industrial development, clustering effects, agglomeration, and other forms of geographical concentration that are more pronounced on Java Island than in regions outside Java (Kuncoro & Wahyuni, 2009;Nurlestari & Oktavilia, 2023). The literature on MNCs spillover effects suggests that positive effects of inter-industrial spillovers are more often found than intraindustry ones (Rojec & Knell, 2018).…”
Section: Estimation Results For Java (National Industrial Corridor) A...mentioning
confidence: 93%